A study of automatic measurement method of RPG (Re-tensile Plastic zone's Generated) Load. Issue 10 (2nd December 2021) - Murakami, Koji; Morishita, Mizuki; Gotoh, Koji
ABSTRACT: Identification of the relationship between fatigue crack propagation rate ( da / dN ) and stress intensity factor range (∆ K ) is inevitable to apply the fracture mechanics approach to assess the growth of fatigue crack growth. The relationship between da / dN and ∆ K is widely applied to evaluate fatigue crack propagation behaviour. To evaluate the fatigue crack growth history under variable loading history, it is necessary to replace ∆ K to the effective stress intensity factor range, which can quantitatively consider fatigue crack opening and closing behaviour. ∆K eff proposed by Elber is well known as the effective stress intensity factor range, but even if ∆K eff is applied to evaluate the fatigue crack propagation behaviour, a threshold value (( ∆K eff )th ) was occurred. On the other hand, it is known that fatigue cracks propagate even at ∆K eff below ( ∆K eff )th under variable loading history. This implies that ∆ K eff is an insufficient parameter to describe fatigue crack propagation behaviour. ∆ K RPG, which has a close relationship with the cyclic plastic behaviour in the vicinity of the crack tip proposed by Toyosada and Niwa, can overcome the shortcomings of ∆K eff even under complicated variable loading history including multiple frequency components. To apply the fatigue crack propagation law with ∆ K RPG as a parameter, it is necessary to experimentally measure the RPG load and identify the propagation law constants (∆ K RPG  =  C (∆ K RPG ) m ) C and m . A conventional method for identifying RPG loads requires the superposition of the hysteresis loop near the crack tip and its reversal loop as measured by the unloading elastic compliance method. However, advanced skills in this method, such as understanding the characteristics of measurement errors associated with loops, is required. In this study, we have proposed an automatic method for measuring the RPG load that is equivalent to manual measurement results by an expert and we have validated the automatic measurement method by comparing the results of automatic measurement using our proposed method with the past conventional measurement results for several materials and loading conditions.